Assessment of arbuscular mycorrhizal association in some fruit and spice plants of Rangamati hill district (Bangladesh Journal of Agricultural Research, 2017)
Rhizosphere soils of some fruit and spice plants from the Hill Agricultural Research Station, Bangladesh Agricultural Research Institute, Raikhali, Rangamati were collected during 2011-12 and 2012-13 for counting Arbuscular Mycorrhizal (AM) spore population, determining colonization (%) in their roots and studying AM structure. Assessment of spore population was done by following the Wet Sieving and Decanting Method. The percentage of AM infection was estimated by root slide technique. The spore number of 100g rhizosphere soil was recorded ranging from 120 in rhizosphere soil of Malta plant to a maximum of 410 in Atafal and Sofeda plants during 2011-12 and from 75 in rhizosphere soil of Phalsa plant to a maximum of 327 in Amlaki plant during 2012-13. Different fruit and spice plants showed different percentages of root colonization by AM fungi. Among the fruit and spice plants, the highest colonization (40%) was found in Jabotica, Phalsa and Sofeda plant, and the lowest colonization (6.6%) was found in Rambutan plant during 2011-12, but in 2012-13 the highest (61.3%) was result was observed in Bilatigab plant and the lowest (18.7%) was in Misti lebu, Malta and Tetul plant. The AM fungal structure in the root system of the selected fruit and spice plants varied in irrespective of fruit and spice species. Some plants had vesicles. Hyphae were present in most of the plants. Some plant species recorded Arbuscules. Both oval and spherical shape vesicles were found in this study.Bangladesh J. Agril. Res. 42(2): 221-232, June 2017